MicroRNAs in atrial fibrillation – have we discovered the Holy Grail or opened a Pandora’s box? - Balan, Alkora Ioana; Scridon, Alina (Frontiers in Pharmacology, 2025)
Atrial fibrillation (AF) causes a heavy socio-economic burden on healthcare systems around the globe. Identification of new preventive, diagnostic, and treatment methods is imperative. In recent years, special attention has been paid to microRNAs (miRNAs) as potential regulators of AF pathogenesis. Through post-transcriptional regulation of genes, miRNAs have been shown to play crucial roles in AF-related structural and electrical atrial remodeling. Altered expression of different miRNAs has been related to proarrhythmic changes in the duration of action potentials and atrial fibrosis. In clinical studies, miRNA changes have been associated with AF, whereas in experimental studies miRNA manipulation has emerged as a potential therapeutic approach. It would appear that, with the advent of miRNAs, we may have found the Holy Grail, and that efficient and personalized AF therapy may be one step away. Yet, the clinical relevance of miRNA evaluation and manipulation remains questionable. Studies have identified numerous miRNAs associated with AF, but none of them have shown sufficient specificity for AF. MicroRNAs are not gene-specific but regulate the expression of a myriad of genes. Cardiac and non-cardiac off-target effects may thus occur following miRNA manipulation. A Pandora’s box might thus have opened with the advent of these sophisticated molecules. In this paper, we provide a critical analysis of the clinical and experimental, epidemiological and mechanistic data linking miRNAs to AF, we discuss the most promising miRNA therapeutic approaches, we emphasize a number of questions that remain to be answered, and we identify hotspots for future research.